Seed-based authentication for mobile clients across multiple devices. Issue 1 (2nd January 2018) - Chen, Longbin; Chen, Li-Chiou; Nassar, Nader
ABSTRACT: Authenticating users for mobile cloud apps has been a major security issue in recent years. Traditional passwords ensure the security of mobile applications, but it also requires extra effort from users to memorize complex passwords. Seed-based authentication can simplify the process of authentication for mobile users. In the seed-based authentication, images can be used as credentials for a mobile app. A seed is extracted from an image and used to generate one-time tokens for login. Compared to complex passwords, images are more friendly to mobile users. Previous work had been done in seed-based authentication which focused on providing authentication from a single device. It is common that a mobile user may have two or more mobile devices. Authenticating the same user on different devices is challenging due to several aspects, such as maintaining the same credential for multiple devices and distinguishing different users. In this article, we aimed at developing a solution to address these issues. We proposed multiple-device authentication algorithms to identify users. We adopted a one-time token paradigm to ensure the security of mobile applications. In addition, we tried to minimize the authentication latency for better performance. Our simulation showed that the proposed algorithms can improve the average latency of authentication for 40% at most, compared to single-device solutions.